The Effect Of Information System Implementation And Integrity On Employee Performance Delay - Asri, Siti Halimahtul; Rizqi, Muhammad Nur; Hurriyaturrohman, Hurriyaturrohman; Yudiana, Yudiana (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
The research was conducted to find out whether the implementation of AIS and integrity has an effect on employee performance. This research was conducted at PT. Gangsar Gol Sejahtera. This type of research uses quantitative methods. The data source in this research uses primary data obtained through distributing questionnaires to PT employees. Gangsar Gol Sejahtera. This research uses convenience sampling techniques. The population of this research is all employees of PT. Gangsar Gol Sejahtera, while the samples taken were employees who could access the accounting information system as many as 30 respondents. Testing in this research was carried out using the SPSS V26 application. The research results show that the implementation of accounting information systems and integrity has a significant positive effect on employee performance. The better the implementation of the accounting information system and the increased employee integrity, the resulting employee performance will also increase so that it can help employees complete their work and responsibilities within the company